Philosophy of the foundations of grammar and jurisprudence and their relation to linguistic achievements - guessoum, youcef (El Omda in Linguistics and Discourse Analysis, 2024)
<section class="text-token-text-primary w-full focus:outline-none [–shadow-height:45px] has-data-writing-block:pointer-events-none has-data-writing-block:-mt-(–shadow-height) has-data-writing-block:pt-(–shadow-height) [&:has([data-writing-block])>*]:pointer-events-auto R6Vx5W_threadScrollVars scroll-mb-[calc(var(–scroll-root-safe-area-inset-bottom,0px)+var(–thread-response-height))] scroll-mt-(–header-height)" dir="auto" data-turn-id="c7675f21-6c21-4171-87ed-5192ce06710e" data-testid="conversation-turn-47" data-scroll-anchor="false" data-turn="user"> <section class="text-token-text-primary w-full focus:outline-none [–shadow-height:45px] has-data-writing-block:pointer-events-none has-data-writing-block:-mt-(–shadow-height) has-data-writing-block:pt-(–shadow-height) [&:has([data-writing-block])>*]:pointer-events-auto [content-visibility:auto] supports-[content-visibility:auto]:[contain-intrinsic-size:auto_100lvh] R6Vx5W_threadScrollVars scroll-mb-[calc(var(–scroll-root-safe-area-inset-bottom,0px)+var(–thread-response-height))] scroll-mt-[calc(var(–header-height)+min(200px,max(70px,20svh)))]" dir="auto" data-turn-id="request-WEB:54cd9541-22be-4ac2-9bea-d51d80033e4e-23" data-testid="conversation-turn-48" data-scroll-anchor="false" data-turn="assistant"> <div class="text-base my-auto mx-auto pb-10 [–thread-content-margin:var(–thread-content-margin-xs,calc(var(–spacing)*4))] @w-sm/main:[–thread-content-margin:var(–thread-content-margin-sm,calc(var(–spacing)*6))] @w-lg/main:[–thread-content-margin:var(–thread-content-margin-lg,calc(var(–spacing)*16))] px-(–thread-content-margin)"> <div class="[–thread-content-max-width:40rem] @w-lg/main:[–thread-content-max-width:48rem] mx-auto max-w-(–thread-content-max-width) flex-1 group/turn-messages focus-visible:outline-hidden relative flex w-full min-w-0 flex-col agent-turn"> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal outline-none keyboard-focused:focus-ring [.text-message+&]:mt-1" dir="auto" tabindex="0" data-message-author-role="assistant" data-message-id="bae32c8a-d0cf-4000-be60-b3c5bff3cd2b" data-message-model-slug="gpt-5-3-mini" data-turn-start-message="true"> The article addresses important issues related to classical and modern linguistic studies, and proposes forward-looking strategies for their development and improvement. It also discusses the relationship between philosophy, metaphysics, and logic on the one hand, and the philosophy of the foundations of grammar and Islamic jurisprudence on the other. Furthermore, it presents the divergence among researchers in this field, who are divided into three main positions: The first group believes that Arabic linguistic studies are authentically rooted in Arab intellectual heritage, originating from the efforts of early scholars, jurists, and philosophers, and later developed through interaction with other scientific philosophies. The second group denies this originality, arguing that Arabs borrowed philosophical and linguistic ideas from other civilizations such as the Greeks and Indians. The third group seeks reconciliation between both views, and this is the position adopted by the article. Finally, the article aims to answer the central problem through a set of findings and recommendations that highlight the interaction between originality and influence in the formation of Arabic linguistic thought.